Being good & being logical : philosophical groundwork for a new deontic logic - Forrester, James W. (Armonk, N.Y. : M.E. Sharpe, 1996)
We all reason about what we ought to do, what should be, and what is permissible, but neither Standard Deontic Logic (SDL) nor its more recent variants adequately represent the principles of our deontic reasoning. In this groundbreaking new work, author James Forrester first explores the shortcomings of standard deontic systems, and concludes that we need a new type of deontic logic; in the second part of the book, he presents a new deontic logic and semantics that fit our deontic reasoning better than standard systems. Finally, in a third section, Forrester sketches some original implications of his new deontic logic for practical reasoning. This book will be of interest to all philosophers, especially those with an interest in questions of moral and practical reasoning.
Pt. I. Problems of Standard Deontic Logic. Ch. 1. What Is Deontic Logic, and Why Should I Care? Ch. 2. Standard Deontic Logic. Ch. 3. What Is Left for Deontic Logic? Ch. 4. 'Ought to Be' and 'Ought to Do'. Ch. 5. Why Deontic Logic Needs a Semantics. Ch. 6. The SDL Semantics of 'Ought to Do' Statements I: Deontically Accessible Worlds. Ch. 7. The SDL Semantics of 'Ought to Do' Statements II: The Principle of Backward Translation. Ch. 8. The SDL Semantics of 'Ought to Do' Statements III: Epistemic Problems. Ch. 9. New Light on Old Problems. Ch. 10. The Semantics of 'Ought to Be' Statements -- Pt. II. A New Deontic Logic. Ch. 11. Rights and What Ought to Be. Ch. 12. Can Duties Be Multiplied Beyond Necessity? Ch. 13. Moral Realism and the Need for a New Semantics. Ch. 14. A New Deontic Semantics. Ch. 15. Being Good and Being Logical: What Deontic Logic Ought to Be -- Pt. III. Deontic Logic and Practical Reasoning. Ch. 16. Deontic Logic and Practical Reasoning.
Includes bibliographical references (p. 322-324) and index.
Keywords: Deontic logic; Ethics; Logic